Evaluation of Two Primer Sets for Amplification of Comammox Nitrospira amoA Genes in Wetland Soils - Lin, Chenshuo; Xu, Hang; Qin, Wei; Xu, Shaoyi; Tang, Xiufeng; Kuang, Lu; Wang, Xinxin; Jiang, Bin; Chen, Junhui; Shan, Jun; Adams, Jonathan; Qin, Hua; et al. (Frontiers in Microbiology, 2020)
After the discovery of complete ammonia-oxidizing (comammox) Nitrospira, detection and assessments of the contribution of comammox Nitrospira communities to nitrogen cycling are in great demand. PCR-based study, which is a common method for the detection of comammox, depends strongly on accurate amplification of the amoA genes from the original DNA samples using appropriate primers. In this study, we reported an evaluation of the performance of two commonly used primer sets, Ntsp-amoA 162F/359R and comaA/B-244f/659r, for amplifying the comammox amoA genes from three representative wetland soils in China (Sangsang (SS), Sanjiang (SJ) and Xianghai (XH)). Our results demonstrated the two primer sets could both successfully amplify the clades with high relative abundances (RA), and further revealed a broadly similar diversity and community composition of dominant comammox operational taxonomic units (OTUs) (RA≥1%) in each of the three wetland soils. However, the clades with low RA, such as the clade A (1.26%) in SJ and the clade B (11.54%) in XH recovered by metagenomic analysis, failed to be amplified using comaA/B-244f/659r, but were successfully amplified and sequenced by using Ntsp-amoA 162F/359. It indicated that Ntsp-amoA 162F/359 compared to comaA/B-244f/659r was more sensitive to the clades of low RA, whereas the former one would overestimate some of clades of low RA, such as the clade A in SS from 26.32% to 50.44% and the clade B in XH from 1.26% to 40.90%. Furthermore, both primer sets showed challenges with significant non-target amplification detected in agarose gels, especially for comammox Clade B amoA genes, implying that we should treat qPCR results based on these primers with caution. Taken together, our study comprehensively compared the performance of the two primer sets on the presence, diversity and structures of comammox amoA genes in three wetland soils, emphasizing the necessity of continued development of new efficient and specific primers for comammox detection in various environments.